Penerapan Metode Customer Relationship Management Berbasis Web Pada Pemasaran Kain Tenun Desa Wisata Lewokluok - Deta, Bernadete; Yohana, Timu (LPPM Institut Pendidikan Nusantara Global, 2025)
The marketing of woven fabrics greatly affects the community's economy, especially in the Lewokluok Tourism village. Marketing of woven fabrics must be done with good and appropriate methods so that they can provide satisfaction to customers. The purpose of this study is to market woven fabrics typical of Lewokluok tourist village using the web-based Customer Relationship Management method. The results of this study that by utilizing CRM, will make weaving galleries more important and expected so that close and open business relationships will be created and better two-way communication. The advantage of Customer Relationship Management is that it can manage all sales, and cutomer relationships in one database.